Acoustic Properties of Absorbing Materials - Piana, Edoardo; Bonfiglio, Paolo; Rychtarikova, Monika (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Thanks to the progress made in materials research and to the introduction of innovative manufacturing technologies, a wide range of sound-absorbing elements are currently available to adjust the acoustic features of an environment. Nowadays, performance is only one of the required specifications, together with environmental compatibility, longevity, and affordable cost. This book collects the most recent advances in the broad-spectrum characterization of sound-absorbing materials used in civil, industrial, and tertiary applications, by means of experimental, numerical, or theoretical studies.